Effects of altitude exposure on total haemoglobin mass in female kayakers - Malczewska-Lenczowska, J.; Sitkowski, D.; Pokrywka, A.; Kryk, T.; Szygula, Z.; Orysiak, J. (2013)
Haemoglobin is one of the key determinant of maximal oxygen uptake. Many studies indicate that natural altitude training may lead to an increase in total hemoglobin mass (tHbmass), although the reported results are contradictory. The purpose of this study was to examine the impact of 17-days classical altitude training on tHb-mass. The subjects of the study (n = 6) stayed at 2011m and trained at 1700-3100m above sea level for 17 days. The following indices were measured: tHb-mass - by optimised CO-rebreathing method according to Schmidt and Prommer, Haemoglobin concentration (Hb) and hematocrit (Ht) in venous blood using a hematological analyser Advia 120; Plasma volumes were computed. All measurements were taken at baseline and on the second day after training camp. Differences in mean changes between consecutive measures were analysed using Wilcoxon`s signed-rank test (p<0.05). Conclusions 1.The tHbmass responds to training under hypoxia conditions. 2.Despite the lack of significant changes in mean value of plasma volume, high individual variability of this parameter indicate that tHb-mass better than Hb concentration reflects effect of exposure and training in hypoxia.